The Role of Bank-based and Market-based Financial Development on Economic Growth of Nepal - Rana, Surya Bahadur (PYC Nepal Journal of Management, 2019)
This study examines the empirical relationship between economic growth and various measures of stock market and banking development in Nepal over the sample period 1987/88 to 2015/16 using a framework of endogenous growth model suggested by Romer (1986), Rebelo (1991) and Pagano (1993). The study finds that stock market size, liquidity and banking development measures predict the economic growth in the context of Nepal. Similarly, the study results show the important role of banking development on economic growth process of Nepal because all indicators of banking development have positive and significant impact on growth. The study results shed light on the fact that both the level of stock market development and the level of banking development can influence the economic growth of Nepal. This finding supports the notion of Levine (1996) which articulates that stock market and banking sector are independently as well as jointly significant in promoting economic growth.